A CRITICAL REVIEW OF TRACING KNOWLEDGE DIFFUSION FLOWS IN ISLAMIC FINANCE RESEARCH: A MAIN PATH ANALYSIS - Bhenu Artha; Fajar Santoso; Ascasaputra Aditya; Wuku Astuti (International Journal of Multidisciplinary Reseach, 2026)
This study provides a critical review of Rejeb et al.'s (2026) research, which uses co-word and main path analysis to trace knowledge diffusion in Islamic finance (IF) literature. The objective of this paper is to evaluate the methodological rigor, theoretical underpinnings, and empirical findings of the original study to identify research gaps and inconsistencies. The research employs a critical literature review methodology to systematically assess and critique the selected paper. The findings indicate that while the original study boasts a novel dual-methodological approach, a comprehensive dataset of 4,422 documents, and a clear thematic architecture by identifying seven distinct clusters, it suffers from notable limitations. Key weaknesses include an exclusive reliance on the Scopus database, uniform citation weighting, language bias, and limited longitudinal or comparative trend analysis. The review concludes that the paper successfully maps the IF research landscape but functions more as a descriptive-analytical study rather than a prescriptive guide, falling short of providing transformative insights into emerging IF domains.